INTERIOR RESTORATION A.A MARAMIS BUILDING MINISTRY OF FINANCE OF INDONESIA: DEVELOPING INTERIOR CONCEPTS WITH THE PRINCIPLES OF CULTURAL HERITAGE RESTORATION - Purnama, Ika Yuni (UI Scholars Hub, 2020)
A.A Maramis is a palace building consisting of 3 floors with the 19th century Empire in Indonesia. This building represents the development of Indonesian architecture in the early 19th century. In the renovation planning that began at the end of 2019, the A.A Maramis building is expected to be a historical reminder of how important this agency is as well as the chronology of events that have occurred in the past in order to increase love for the nation and the motherland. In the planning of restoration is expected to become one of the attractive and educative tourism destination. Restoration of A.A. Maramis building refers to the concepts and principles of Cultural Heritage. This study uses qualitative methods and interdisciplinary approaches include history, culture, and aesthetics. The renovation and development as well as the use of the interior or interior is a place to preserve, present and convey information about the travel history of the Ministry of Finance in developing the nation and state of Indonesia.